PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PELATIHAN TERHADAP KOMITMEN ORGANISASI DAN KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KOTA DENPASAR - Ni Ketut Eny Purnawati; Gede Suparta; Putu Ngurah Suyatna Yasa (Universitas Warmadewa, 2017)
Given the importance of commitment organization and employee performance, the issue which is of particular interest are the factors that incluence it, among others, transformational leadership style and training. Otherwise in Sekretariat Daerah Kota Denpasar an effort to get employess who have the commitment organization and high performance, have noticed transformational leadership and training. The formulation of the problem in this research is whether transformational leadership influence on commitment organization, whether training influence on commitment organization, whether transformational leadership influence on empoloyee performance, whether training influence on employee performance, commitment organization influence on employee performance, whether transformational leadership influence on employee performance by mediation commitment organization and whether training influence on employee performance by mediation commitment organization. And to answer the problem, we conducted research with 60 respondence. The method used collected by questionnaire. The analysis technique used is Parsial Least Square (PLS) Version 20. Based on the results obtained conclusions include : transformational leadership have positive influence and not significant influence to commitment organization, training have positive influence and not significant influence to commitment organization, transformational leadership have positive influence and significant influence to employee performance, training have positive influence and not significant influence to employee performance, commitment organization have positive influence and significant influence to commitment organization, commitment organization is partial mediation to influence between transformational leadership to employee performance, commitment organization is partial mediation to influence between training to employee performance.